2011
DOI: 10.1002/mnfr.201100292
|View full text |Cite
|
Sign up to set email alerts
|

High dose of dietary resveratrol enhances insulin sensitivity in healthy rats but does not lead to metabolite concentrations effective for SIRT1 expression

Abstract: These results suggest that the improved insulin sensitivity after dietary administration of 300 mg resveratrol/kg body weight does not involve increased protein expression of SIRT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Resveratrol, a natural compound found in grapes and red wine has been shown as an effective SIRT1 activator (Howitz et al, 2003). Numerous studies conducted on animals demonstrated that resveratrol improves glucose metabolism (Baur and Sinclair, 2006; Baur et al, 2006; Barger et al, 2008; Andersen et al, 2011; Kang et al, 2012; Marchal et al, 2012), reduces inflammation (Rivera et al, 2009), reverses non-alcoholic fatty liver disease (Bujanda et al, 2008) and prevents obesity (Dal-Pan et al, 2010). On the other hand the results of clinical studies using resveratrol are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, a natural compound found in grapes and red wine has been shown as an effective SIRT1 activator (Howitz et al, 2003). Numerous studies conducted on animals demonstrated that resveratrol improves glucose metabolism (Baur and Sinclair, 2006; Baur et al, 2006; Barger et al, 2008; Andersen et al, 2011; Kang et al, 2012; Marchal et al, 2012), reduces inflammation (Rivera et al, 2009), reverses non-alcoholic fatty liver disease (Bujanda et al, 2008) and prevents obesity (Dal-Pan et al, 2010). On the other hand the results of clinical studies using resveratrol are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of in vivo studies where insulin sensitivity was diminished (as a consequence of HFD or STZ-induced diabetes), RES lowered glucose and/or insulin levels and/or improved insulin sensitivity independently of dose and exposition time (Supplementary Table ), particularly in rodents [165,184, 194,196,197,199-205]. In one study, AMPK seemed to be required for the insulin sensitivity enhancing effect of RES in mice [206].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…It was found that in HFD-fed Wistar rats, resveratrol (50 or 100 mg/kg/day) treatment for 13 weeks significantly suppressed body weight gain [26]. Andersen et al showed that resveratrol treatment (300 mg/kg/day) in male Wistar rats for 8 weeks decreased the fasting serum insulin level and insulin resistance [27]. In another study, resveratrol treatment (400 mg/kg/day) for 9 weeks reduced body weight and enhanced insulin sensitivity, as measured by a hyperinsulinemic euglycemic clamp in C57BL6/J mice fed a HFD [28].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…First, the doses of resveratrol that were used in the animal experiments were very broad, ranging from 2.5 to 400 mg/kg/day [26,27,28,50]. We decided to choose the dose of 100 mg/kg/day because it is a middle and safe dose that was suggested by previous studies [ 26,27,28,50,51].…”
Section: Accepted Manuscriptmentioning
confidence: 99%